Mean free path in soccer and gases - Luzuriaga, J. (IOP Publishing, 2010)
Fil: Luzuriaga, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina